Water-Soluble J-Type Rosette Nanotubes with Giant Molar Ellipticity. - Borzsonyi, Gabor; Beingessner, Rachel L.; Yamazaki, Takeshi; Jae-Young Cho; Myles, Andrew J.; Malac, Marek; Egerton, Ray; Kawasaki, Masahiro; Ishizuka, Kazuo; Kovalenko, Andriy; Fenniri, Hicham (Journal of the American Chemical Society, 2010)
A new self-assembling tricyclic module (×K1) featuring the Watson-Crick H-bonding arrays of guanine and cytosine fused to an internal pyridine ring was synthesized. When dissolved in water at room temperature, this module rapidly self-assembles into hexameric rosettes, which then stack to form J-type rosette nanotubes (RNTs) with increased inner/outer diameters and the largest molar ellipticity ever reported (4 × 10 deg·M·m). Using a combination of imaging and spectroscopic techniques we established the structure of ×K1-RNT and have shown that the extended π system of the self-assembling module resulted in a new family of J-type RNTs with enhanced intermodular electronic communication.